2015
DOI: 10.1186/s13071-015-1250-2
|View full text |Cite
|
Sign up to set email alerts
|

Ecology and spatiotemporal dynamics of sandflies in the Mediterranean Languedoc region (Roquedur area, Gard, France)

Abstract: BackgroundPhlebotomine sandflies are hematophagous insects widely present in Western Mediterranean countries and known for their role as Leishmania vectors. During the last ten years, the risk of leishmaniasis re-emergence has increased in France. However, sandfly biology and ecology in the South of France remain poorly known because the last detailed study on their spatiotemporal dynamics was performed over 30 years ago. The aim of the present study was to update our knowledge on sandfly ecology by determinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 32 publications
2
44
0
3
Order By: Relevance
“…It was not possible to make any conclusion for the other months (May, August and September) due to the low number of individuals captured. These differences observed between June and July may be due to environmental variations as it was observed in previous study [36]. The individuals captured in June and July have certainly emerged at the end of May and June, respectively.…”
Section: Discussionmentioning
confidence: 49%
“…It was not possible to make any conclusion for the other months (May, August and September) due to the low number of individuals captured. These differences observed between June and July may be due to environmental variations as it was observed in previous study [36]. The individuals captured in June and July have certainly emerged at the end of May and June, respectively.…”
Section: Discussionmentioning
confidence: 49%
“…The number of trapped sand flies was always very small, usually only 1 or 2 specimens. In most studies, P. mascittii is found in low population densities [41][42][43][44]. The low density may be due to the specific ecological niche they are adapted to (caves, tunnels and natural barns) [41,45].…”
Section: Discussionmentioning
confidence: 99%
“…In the European context, it has been demonstrated that the density of Phlebotomus ariasi at a particular sampling location is affected by both minimum and maximum temperatures and to some extent by RH (Prudhomme et al, 2015). South facing slopes, wall vegetation, soil type and neighbouring land cover precipitation may also be important factors in determining local abundance of this and other species (Ballart et al, 2014).…”
Section: Leishmaniamentioning
confidence: 99%